Carbon-family materials for flame retardant polymeric materials. (June 2017) - Wang, Xin; Kalali, Ehsan Naderi; Wan, Jin-Tao; Wang, De-Yi
Abstract: As an abundant and attractive element, the emergence of new carbon-based materials brings revolutionary development in material science and technology. Carbon-based materials have spawned considerable interest for fabricating polymer composites/nanocomposites with greatly improved mechanical, thermal, gas barrier, conductivity, and flame retardant performance. In this review, the importance of carbon-based materials and the necessity of fire resistance for polymeric materials are initially introduced. Then, the fundamental flame retardant mechanisms and experimental analytical techniques are described to understand the relationship between structures and flame retardant properties. The main section is dedicated to the preparation and properties of multifunctional polymer composites/nanocomposites with carbon-based materials, with special emphasis on the flame retardant properties of these materials. A wide variety of carbon-based materials are discussed for use in flame retardant polymer nanocomposite, including graphite, graphene, carbon nanotubes, fullerenes as well as some new emerging carbon forms (carbon nitride, carbon aerogels, etc). Finally, a brief outlook at the developments in carbon-based materials for flame retardant polymeric composites is given by discussing the major progress, opportunities, and challenges.